Pemanfaatan Multimedia Interaktif Dalam Meningkatkan Kualitas Pembelajaran Online - Sukmawati, Anis; Fitriyah, Lailatul; Aziz Rifai, Abdul (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2023)
Online learning is an alternative to continue the education process during the pandemic. The declinein the quality of learning is caused by the delivery of material that only relies on applicationsonlinemeeting combined with presenting material through presentation slides. This method places studentsas listeners who tend to be passive because learning is less interactive. Therefore, by using theliterature study research method (library research), in this article we will explain how educators canutilize interactive multimedia to improve the quality of online learning. From the results of thisresearch, it was concluded that there are several interactive media models that can be utilized, suchas; 1) Tutorial Model; 2) Model Drills; 3) Simulation Model; and 4) Instructional Games Model. Ofthe four models, the instructional games model is likeKahoot, Educandy, Wordwall, become a modelthat is more popular with students. Thus, the recommendation to educators is that further efforts areneeded to improve the way material is delivered in online learning, taking into account students' needsand learning styles and practicing digital skills to be able to utilize multimedia so that the learningprocess can run more effectively and interactively.